Implementation of E-Procurement in Micro, Small and Medium Enterprises (MSMEs) in Yogyakarta - Reni Listyawati; Uum Helmina Chaerunisak; Sri Lestari Yuli Prastyatini (IMPACTS: International Journal of Empowerment and Community Services, 2023)
PurposeCommunity Service (Abdimas) activities carried out at the MSME "Dapoer Tania" aim to improve marketing methods by increasing the intensity of utilizing social media, increasing the capacity for product and packaging innovation, and implementing operational procedures for the e-procurement system by considering certain criteria for selection. digital supplier that produces a standardized and structured system at "Dapoer Tania" Methods -Implementation of activities is carried out through several stages, namely field observation, training and mentoring. The first stage was collecting data using survey and interview methods. The survey was carried out through direct monitoring of the situation that actually occurred in the MSME "Dapoer Tania". This monitoring is carried out so that it can be described what needs need to be in the information system to be built. Next is the interview. Interviews were conducted through discussions with owners regarding obstacles, business processes and implementation of e-procurement systems and checking existing SOPs in MSMEs. The second stage is carried out after identifying the problems found in the first stage. The third stage is carried out after field observations and training are completed. Results and discussions –Technological developments have brought convenience to services so that many companies are adopting e-procurement as a supply chain support to be able to adapt to market changes and to achieve business goals, such as operational efficiency, sustainability and profitability. Many companies are adopting e-procurement because of its ability to streamline supply chain networks. The emergence of e-procurement has created a higher profile for supply management as well as increased visibility to a company's top management. By adopting this technology, it has influenced organizational performance, both directly and indirectly. The results of this service also show that the marketing method training program by increasing intensity utilizing social media, Conclusion -E-procurement brings transparency and effectiveness in the supply chain and makes a significant contribution to supply chain performance. In addition, e-procurement also allows companies to measure and monitor orders, such as processing time, order delivery time, and current status. Therefore, the implementation of e-procurement in MSMEs plays an important role and will have an impact on improving supply chain performance in MSMEs.